Influence of load-induced cracks coupled or not with top-casting-induced defects on the corrosion of the longitudinal tensile reinforcement of naturally corroded beams exposed to chloride environment under sustained loading. (March 2020) - Zhang, Wulong; François, Raoul; Yu, Linwen
Abstract: This paper discusses the effect of both load-induced cracks and top-casting-induced defects on the corrosion characteristics of the tensile bars in reinforced concrete beams under sustained loading and exposure to a chloride environment. Four reinforced concrete beams exposed to climate accelerated natural corrosion were used in the present work. The cracking maps, chloride profiles and cross-sectional loss of four beams were studied and compared with each other. Experimental results show that the presence of load-induced cracks is not the sole cause of early propagation of corrosion. As a result, top-casting-induced defects are the most significantly impacting factor accelerating the deterioration of reinforced concrete. With top-casting-induced defects, corrosion starts at service cracks and then develops preferentially at the bottom surface of the tensile bar. Without top-casting-induced defects, corrosion starts at service cracks but does not develop along the tensile bar. It is only when the chloride content at the depth of reinforcement reaches a critical value that corrosion develops along the tensile bar – preferentially at the outside surface of the rebar because of its probable higher chloride content.